DETRADICIONALIZATION OF GENDER ROLES IN BIOGRAPHICAL TRAJECTORIES OF MALE SOCIAL WORKERS - Mažeikienė, Natalija; Dorelaitienė, Agnė (Acta Paedagogica Vilnensia, 2012)
Formation of the new economy in post-industrial society and neoliberal restructurization in labour market transforms the traditional gender division of labour and partly softens the extreme form of the division, i.e. segregation, in education, social work, nursing, and care. Social work continues to be treated as a feminized area of professional activity and shows a profound professional segregation into female and male professions. The study on professional identity of male social workers, presented in this article, has revealed that the process of becoming a social worker among males is a sequence of complex decisions and experiences accompanied by critical incidents and changes in their life trajectories. Such a complexity is caused by the ideal norms of hegemonic masculinity that frame the actual social structures and are introduced into the processes of socialization, formal and hidden curriculum and habituation with the aim to form the masculine habitus. The feminine and masculine habitus is formed through a symbolic and practical construction, upbringing, socialization as girls and boys adopt feminine and masculine constructs of thinking and behaviour, which are reinforced in the process of habituation. It establishes and legitimizes normative masculine and feminine biography, normative educational and career trajectories. The empirical research presented in the article has demonstrated that the masculine habitus manifests itself as the striving and attempt of male participants of the research to find their professional identity without crossing the limits of masculine normative identity. Nevertheless, the trajectories of educational experience and life events of the research participants have revealed the choice in favour of a non-traditional occupation as a defeat of the traditional gender division of labour by opposing to “normality” – by undergoing and overcoming the crisis. Professional biographies of male social workers have disclosed the balancing of the males between the normative trajectory of masculine behaviour and striving to find the real “self”. At this point, the biographical narrative of male social workers has revealed itself as a reflexive project which discloses a painful tension between the subjective reality of the inner world, life events and social structures, dominating discourses. The results of the study prompt the further development of research and the creation of a new educational reality, change of the habitus and content of the curriculum in order to create the prerequisites for strengthening the gender roles and detraditionalization of the labour market by adapting to the changes in the labour market that appear in postmodern society and post-industrial economy.
Keywords: gender division of labour; vertical and horizontal proffessional segregation; habitus; gender socialization; habituation; biographical method; hegemonic masculinity